In-season internal load and wellness variations in professional women soccer players: Comparisons between playing positions and status - Fernandes, Renato; Brito, João Paulo; Vieira, Luiz H. Palucci [UNESP]; Martins, Alexandre Duarte; Clemente, Filipe Manuel; Nobari, Hadi; Reis, Victor Machado; Oliveira, Rafael (MDPI, 2021)
The internal intensity monitoring in soccer has been used more in recent years in men’s football; however, in women’s soccer, the existing literature is still scarce. The aims of this study were threefold: (a) to describe the weekly variations of training monotony, training strain and acute: chronic workload ratio through session Rated Perceived Exertion (s-RPE); (b) to describe weekly variations of Hooper Index [stress, fatigue, Delayed Onset Muscle Soreness (DOMS) and sleep]; and (c) to compare those variations between playing positions and player status. Nineteen players (24.1 ± 2.7 years) from a Portuguese BPI League professional team participated in this study. All variables were collected in a 10-week in-season period with three training sessions and one match per week during the 2019/20 season. Considering the overall team, the results showed that there were some associations between Hooper Index categories and s-RPE like stress or fatigue (0.693, p < 0.01), stress or DOMS (0.593, p < 0.01), stress or s-RPE (−0.516, p < 0.05) and fatigue or DOMS (0.688, p < 0.01). There were no differences between all parameters in playing positions or player status. In conclusion, the study revealed that higher levels of fatigue and DOMS occur concurrently with better nights of sleep. Moreover, any in-season variations concerning internal load and perceived wellness seems independent of position or status in outfield players. The data also showed that the higher the players’ reported stress, the lower the observed s-RPE, thus possibly indicating a mutual interference of experienced stress levels on the assimilation of training intensity by elite women soccer players.
Keywords: Fatigue; Female; Muscle soreness; Perceived exertion; Sleep; Stress; Training monotony; Training strain